2020
DOI: 10.1002/jlb.3a0520-745rr
|View full text |Cite
|
Sign up to set email alerts
|

Classically activated mouse macrophages produce methylglyoxal that induces a TLR4- and RAGE-independent proinflammatory response

Abstract: The highly reactive compound methylglyoxal (MG) can cause direct damage to cells and tissues by reacting with cellular macromolecules. MG has been identified as a biomarker associated with increased sepsis-induced mortality. Patients undergoing septic shock have significantly elevated circulating MG levels compared to postoperative patients and healthy controls. Furthermore, MG has been implicated in the development of type II diabetes mellitus and Alzheimer's disease. Because MG is generated during glycolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Using a polyclonal antibody specific for RAGE (#ab37647, Abcam, Cambridge, United Kingdom), we detected RAGE in mouse lung tissue (Figure 2A). Conversely, in mouse peritoneal macrophages, the antibody detects a similar band, but slightly lower in molecular weight, that we initially speculated might be soluble RAGE in our earlier publication 52 . However, further investigation determined that this band was equivalently present in lysates from both WT and RAGE −/− peritoneal macrophages (Figure 2B), indicating that this is a nonspecific band.…”
Section: Matters Of Controversymentioning
confidence: 56%
See 3 more Smart Citations
“…Using a polyclonal antibody specific for RAGE (#ab37647, Abcam, Cambridge, United Kingdom), we detected RAGE in mouse lung tissue (Figure 2A). Conversely, in mouse peritoneal macrophages, the antibody detects a similar band, but slightly lower in molecular weight, that we initially speculated might be soluble RAGE in our earlier publication 52 . However, further investigation determined that this band was equivalently present in lysates from both WT and RAGE −/− peritoneal macrophages (Figure 2B), indicating that this is a nonspecific band.…”
Section: Matters Of Controversymentioning
confidence: 56%
“…Initially, it was reported that RAGE‐deficient mice on a CD‐1 background strain were slightly protected against a lethal dose of LPS 15 . However, a subsequent study originating in our laboratory failed to distinguish a significant difference between WT and RAGE‐deficient mice using a different mouse background (C57BL/6J) and a lower LPS dose (50 vs. 20 mg/kg) 52 . Another variation of this basic model of sepsis is the injection of a low dose of LPS to prime the mice, followed by a challenge with a second higher LPS dose.…”
Section: Physiologic Relevance Of Rage In Diseasementioning
confidence: 92%
See 2 more Smart Citations
“…Given the critical role of macrophage-mediated Aβ clearance in both murine models and patients with AD, IL-34 might be relevant to innate immune responses in AD ( 27 ). Besides, in clinical studies, the highly reactive compound, methylglyoxal, has been implicated in the development of AD and methylglyoxal might be produced by macrophages during sepsis and further fasten the pathological process of AD ( 28 ).…”
Section: Roles Of Peripheral Immune Cells On Neurodegenerative Diseasmentioning
confidence: 99%